PERSEPSI SISWA TERHADAP KOMPETENSI PEDAGOGIK GURU MATA PELAJARAN SEJARAH DI SMA NEGERI 8 PEKANBARU - Amirul Syafiq; Isjoni Isjoni; Tugiman Tugiman (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: SMA Negeri 8 Pekanbaru is located at Jalan Abdul Mouse number 14, Kelurahan Cinta Raja, Sail District of Pekanbaru City, with the ownership status of Government of Riau Province, which was established in November 26, 1975 with founding decision 0261/0/1975. The purpose of this study is to determine students' perception of the pedagogical competence of history subjects taken from the Ordinance of the Minister of National Education of the Republic of Indonesia No. 16 of 2007 on Academic Qualification Standards and Teacher Competences. The research approach used in this research is quantitative research. Use descriptive (exposure) method. The results of the study obtained by history subject teachers at SMA Negeri 8 Pekanbaru have good abilities in teacher pedagogical competence.Key Words: Students' Perceptions Of Pedagogical Competence In History Subject Teachers In SMA Negeri 8 Pekanbaru